A long time coming - Elkins, Aaron J. (Thomas & Mercer, 2018)
Art curator Val Caruso is not a happy camper. His promotion has just been nixed, his divorce has become final, and he's dug himself into a nice little rut for his fortieth birthday. The uplift? A trip to Milan to help Holocaust survivor Sol Bezzecca recover a pair of cherished sketches by Renoir. They'd once been given to Sol's family by the then-unknown artist, looted by the Italian Fascist militia, and now after decades in hiding have turned up for auction. It's Val's job to get them back.